Основные принципы анализа рисунка капиллярной сети - Соколов, А. А.; Шушляпина, Н. О. (ХНУРЕ, 2019)
The possibilities for developing a computer system for automated analysis of capillaroscopic images and the possible determination of the relationship between changes in the capillaroscopy pattern and pathologies of ENT organs are described.
Keywords: рисунок; сеть капилярная; анализа рисунка капиллярной сети